Tax Morality as a Moderator in Mitigating Tax Evasion: The Role of the Self-Assessment System and Tax Audits - Amin Dara; Fitriani Sardju; Zainuddin Zainuddin (Cita konsultindo, 2024)
This study analyzes the influence of the Self-Assessment System (SAS) and Tax Audits on Tax Evasion, with Tax Morality as a moderating variable. The research was conducted at the KPP Pajak Pratama Ternate with a sample of corporate taxpayers. Data were collected through questionnaires distributed to corporate taxpayers and analyzed using multiple regression to test the direct effects of SAS and Tax Audits on tax evasion and moderation regression to examine the moderating role of Tax Morality in these relationships. The results show that SAS has a significant negative effect on tax evasion, indicating that better implementation of SAS leads to lower levels of tax evasion. Tax Audits also have a significant negative effect, with more intensive tax audits reducing tax evasion. However, the moderation analysis reveals that Tax Morality does not significantly moderate the relationship between SAS and tax evasion. On the other hand, Tax Morality significantly moderates the relationship between Tax Audits and tax evasion, reinforcing the negative effect of tax audits on reducing tax evasion. This study suggests that tax authorities should prioritize strengthening oversight through effective audits and efforts to enhance tax morality. Combining well-implemented SAS, intensive tax audits, and promoting tax morality could reduce tax evasion.